2019
DOI: 10.1088/1748-9326/aafbb6
|View full text |Cite
|
Sign up to set email alerts
|

Seeing is not always believing: crop loss and climate change perceptions among farm advisors

Abstract: As climate change is expected to significantly affect agricultural systems globally, agricultural farm advisors have been increasingly recognized as an important resource in helping farmers address these challenges. While there have been many studies exploring the climate change belief and risk perceptions as well as behaviors of both farmers and agricultural farm advisors, there are very few studies that have explored how these perceptions relate to actual climate impacts in agriculture. Here we couple survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…8). This could support the idea that certain areas are insuring more due to perceived risk (Niles et al, 2019) even if losses remain static over time. Moreover, counties in Nebraska report a larger proportion of their indemnities due to hail as compared with other Ogallala counties (Fig.…”
Section: Spatially Heterogeneous Regions Of Risksupporting
confidence: 59%
See 1 more Smart Citation
“…8). This could support the idea that certain areas are insuring more due to perceived risk (Niles et al, 2019) even if losses remain static over time. Moreover, counties in Nebraska report a larger proportion of their indemnities due to hail as compared with other Ogallala counties (Fig.…”
Section: Spatially Heterogeneous Regions Of Risksupporting
confidence: 59%
“…8), agricultural advisors and farmers still rely heavily on recent experiences and loss (Marx et al, 2007;Coles and Scott, 2009). Moreover, perceived adaptation and/or farmer needs are positively correlated with weather variability, indicating the usefulness of assessing past crop losses (Niles et al, 2019). Near-term memory of losses due to drought and hail are important to producers in their medium to long-term adaptation and uptake of crop insurance, in addition to other operational and tactical management strategies (Taylor et al, 1988;Prokopy et al, 2013;Brown et al, 2017).…”
Section: Implications For Agricultural Risk Managementmentioning
confidence: 99%
“…Even among agricultural advisors or extension professionals who work closely with farmers, perceived weather variability is positively correlated with crop loss, while perceptions for adaptation and future farmers' needs are consistently correlated with weather variability perceptions (Niles et al 2019). Therefore, more recent and significant crop losses and their associated COL may be most salient to farmers in influencing management changes (Niles et al 2019). Using this knowledge, producers may elect to reduce their risk by shifting production systems, increasing crop insurance coverage, changing varieties of crops (e.g.…”
Section: Risk Management Implicationsmentioning
confidence: 99%
“…While evidence indicates that hurricanes are becoming more intense due to climate change, land managers may still be reluctant to implement practices that promote resilience to these events. Diverse factors can influence land managers and advisors to adopt or promote practices that are considered more resilient to climate change and extreme weather events [13], but higher perceived risk of climate and weather impacts has been repeatedly found to increase positive attitudes towards adaptation [14][15][16][17][18].…”
Section: Risk Perception and Climate Change Adaptationmentioning
confidence: 99%
“…Additionally, the more removed, or "psychologically distant" an individual is from an event in terms of time, space, social distance, and certainty, the less influence that event and related risk perception has on decision making [19], and decisions regarding climate change adaptation tend to be driven by concerns surrounding local impacts [13,20]. For example, Haden and coauthors [15] found that farmers in California were more likely to be willing to adopt adaptation practices based on specific local climate conditions, such as water availability and summer temperatures, and Niles and coauthors [18] found that perceived weather variability had a significant influence on agricultural advisors' perception of the need for farmers to adapt.…”
Section: Risk Perception and Climate Change Adaptationmentioning
confidence: 99%